The corporeal and the carnivalesque: the 2004 exposition of St. Francis Xavier and the consumption of history in postcolonial Goa - Gupta,Pamila (2017)
To enter Old Goa during the 2004 Exposition of St. Francis Xaviers Sacred Relics is to experience a world where the corporeal and the carnivalesque coalesce. It is a ritual and religious space wherein the corpse of a 16th century Jesuit missionary-turned-saint takes center stage: pilgrims and tourists stand in the same line to see Xaviers corpse and touch his glass casing, Goas (Portuguese) colonial legacy is exhibited for public consumption, Catholic religious services and lectures on this missionarys biography in a variety of languages take place at regular intervals, makeshift stalls sell numerous iconic objects associated with the saint, and finally, the uncertainty of Xaviers fate is exposed. In this article, I explore the many facets of this exposition of Goas patron saint, suggesting that by taking part in these highly ritualized acts focused on Xavier, tourists and pilgrims simultaneously transform the space of Old Goa, consume its Portuguese past, and become part of history-in-the-making in the face of the increasing fragility of his corpse. Although this paper is based on ethnographic research conducted in 2004, its themes remain relevant given that Xaviers last decennial exposition was staged in 2014-2015, and will continue to take place at ten-year intervals.